Administration of a herbal formulation enhanced blastocyst implantation via IκB activation in mouse endometrium - Songhee Jeon; Quan Feng Liu; Hua Cai; Ha Jin Jeong; Su-Hyun Kim; Dong-Il Kim; Ju-Hee Lee (BMC, 2020)
Abstract Background BaelanChagsangBang (BCB), a herbal formulation consisting of eleven herbs, may be prescribed as a reproductive functional supplement to improve ovulation and implantation during the treatment of infertility and recurrent abortion in Korean Medicine. This study aimed to investigate the effects and action mechanisms of water-extracted BCB on endometrial receptivity and blastocyst implantation under normal conditions and in a mifepristone (RU486)-induced implantation failure murine model. Methods In vitro, the antioxidant potentials of BCB were evaluated using DPPH and superoxide anion radical scavenging assays and a DCFH-DA assay, and the cytotoxic and cytoprotective effects of BCB were confirmed using an MTT assay. In vivo, C57BL/6 female mice (n = 6 per group) orally received BCB (300 mg/kg/day), a dose similar to that used clinically, from 7 days before pregnancy until the end of the experiment. On day 4 of pregnancy, RU486 (4 mg/kg) was injected subcutaneously to induce implantation failure. The effect of BCB on embryo implantation was evaluated by implantation rate analysis, histological examination, and western blotting of uterus tissues. Results BCB water extract showed strong anti-oxidative and cytoprotective effects in vitro. In vivo administration of BCB water extract increased the number of newborn pups in BCB-treated mice versus sham-treated mice under normal conditions and improved the number of implantation sites in pregnant mice despite RU486 injection. BCB increased the protein levels of cyclooxygenase-2 and inducible nitric oxide synthase through IκB activation. Moreover, the expression levels of matrix metalloproteinases at uterus implantation sites were up-regulated in the BCB-treated group as compared with those in the RU486-treated group. Conclusion These results show BCB improved embryo implantation through IκB activation in our mouse model and suggest that BCB has therapeutic potential in the context of poor endometrial receptivity.